A Detection method based on Control Flow Graph for Cisco IOS Security - Sheng-li Liu; Xiang Gao; Cheng Zeng; Li-gen Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Aiming at the problem of current analysis and detection techniques against Cisco IOS security are not suitable for IOS integrality attack, this paper focuses on the Cisco IOS security detection techniques based on Control Flow Graph. First, the constructing method of Control Flow Graph is introduced. Then, a method to extract non-executed malicious code is proposed, which improves the effectiveness and accuracy of the analysis of malicious code. It provides support for rapid and effective detection of IOS integrality attack. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4561